Normative framework guide: responsibility of businesses concerning human rights, labour exploitation and human trafficking - Lietonen, Anni (Publication series, 2020)
This normative framework guide provides a summarised overview of existing legal frameworks outlining businesses’ responsibilities with regard to human rights, with a focus on labour exploitation and trafficking in human beings.